Antimagicness for a family of generalized antiprism graphs - Dominique Buset; Mirka Miller; Oudone Phanalasy; Joe Ryan (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2014)
An antimagic labeling of a graph G=(V,E) is a bijection from the set of edges E to the set of integers {1,2,…, |E|} such that all vertex weights are pairwise distinct, where the weight of a vertex is the sum of all edge labels incident with that vertex. A graph is antimagic if it has an antimagic labeling. In this paper we provide constructions of antimagic labelings for a family of generalized antiprism graphs and generalized toroidal antiprism graphs.